Advancements in Nanopore Technology for Virus Detection - Che, Yiheng; Li, Zhenhua; Xie, Sijia; Chen, Chang (Current Nanoscience, 2024)
Background: The spread of infectious diseases caused by viruses is always a global concern to public health. Developing affordable, accurate, fast and effective technologies for virus detection is crucial in reducing virus transmission. A nanopore is a sensor that can identify target molecules at a single molecule level, often used for genome sequencing and early disease detection. Nanopores are classified in two types: biological nanopores, ideal for detecting viral nucleic acid sequences, and solid-state nanopores primarily used to detect viral particles. Methods: In this review, we first provide a brief overview of the properties and fundamental principles of these two types of the nanopore. Then, we focus on the application of nanopores in viral nucleic acid sequencing and the quantitative detection of viral nanoparticles. Additionally, we discuss new strategies combining nanopore sensors with other technologies, which greatly improve the sensing performance. Results: A literature review on the application of nanopores in controlling viral epidemics is provided. The pros and cons of biological nanopores and solid-state nanopores are summarized, respectively, and the opportunities of integrating novel technologies with nanopore sensors to enhance the latter are addressed in this paper. Conclusion: Owing to significant advancements in nanotechnology and integration with other technologies such as machine learning, nanopore sensors are becoming widely applied in virusesrelated analysis. In the long term, nanopore sensors are expected to play an important role in the field of virus detection and analysis.
Keywords: resistive pulse sensing